Pengaruh Model Pembelajaran Simulasi terhadap Pengetahuan dan Keterampilan Penanganan Cedera Ankle sprain Mahasiswa Penjas - Budiman Budiman; Zainal Abidin; Evi Lestaria (Jurnal Sporta Saintika, 2025)
This study aimed to analyze the effects of simulation-based learning models on improving the knowledge and skills of physical education students in managing ankle sprain injuries. The study employed a quantitative approach using an experimental method with a Pre-Experimental Design of the one-group pretest-posttest design type. The research subjects were physical education students who received simulation-based learning treatment in sports injury management. Data collection techniques included knowledge tests, skill observations, and documentation. Data analysis was conducted using descriptive and inferential statistics in IBM SPSS Statistics, including normality and homogeneity tests, Paired-Samples t-tests, and N-Gain tests. The results showed an increase in students’ average knowledge scores from 62.40 to 84.75 with an N-Gain score of 0.59 in the moderate category. In the skills aspect, the average score increased from 58.20 to 86.10 with an N-Gain score of 0.67 in the moderate category. The Paired Sample t-test result showed a significance value of 0.000 < 0.05, indicating that the simulation learning model had a significant effect on improving students’ knowledge and skills. Therefore, the simulation learning model is considered effective in enhancing the competence of physical education students in handling ankle sprain injuries through interactive, contextual, and experience-based learning.